PERILAKU OVERPROTEKTIF ORANG TUA TERHADAP PENYESUAIAN DIRI PADA USIA REMAJA - Majidah S, Khotimatul; Sitohang, Rhea Aquilla Fawaz; Ritonga, Hajijah Adelina (Early Stage, 2023)
Children are a gift from God given to a family. Families must provide love and good education for children. Parents have an important role in shaping the personality and development of children. The actions of parents in giving love and education about the values of religious and socio-cultural life that are given are the right treatment to prepare children to become good individuals. Parents act as the first teachers for children. The way children think and behave is influenced by parental upbringing which will shape the child's personality. In fact, there are family problems between children and parents. One of them is the overprotective attitude of parents towards their children. Overprotective is a form of excessive protection given to children. In fact, parents behave like that because they really love and are afraid if their child does things that they don't want, but the attitude of parents is sometimes misinterpreted by the child so that the child feels burdened and can affect development.